THE STUDENTS’ RESPONSES ON THE USE OF VIDEO CONFERENCE IN LEARNING ENGLISH - Purnama, I Gusti Agung Vony (LITERA : Jurnal Bahasa Dan Sastra, 2021)
ABSTRACTThis study aims to investigate the students’ responses to the use of video conference MicrosoftTeams Meeting as a tool in conducting distance learning for English subject. Some theories onthe students’ responses and the results of the previous studies were used as the literaturereviews. Students' interviews were used as the data source of this study. The sampling methodwas used in this study. The finding shows that there were positive and negative responses onthe use of video conference as a tool in English learning subject. There were positive responsesregarding the use of materials on the online meeting through Microsoft Teams, positiveresponse based on the students' character, and also positive response based on the method usedin Microsoft Teams meeting. Moreover, students felt more comfortable and enjoyed the onlineclass meeting because they can face the lecturer virtually without afraid of being criticized bythe other students. On the other hand, it was also revealed the negative responses on the limitedtime given particularly in practicing writing skill, negative response based on student'scharacter, and negative responses regarding the lack of the internet connection in conductingthe teaching and learning process on the Microsoft Teams meeting.Key words: Students’ responses, Distance learning, Microsoft Team MeetingABSTRAKPenelitian ini bertujuan untuk mengetahui tanggapan siswa terhadap penggunaan konferensivideo Microsoft Teams Meeting sebagai alat dalam melakukan pembelajaran jarak jauh untukmata kuliah bahasa Inggris. Beberapa teori tentang tanggapan siswa dan hasil penelitiansebelumnya digunakan sebagai bahan kajian pustaka. Wawancara siswa digunakan sebagaisumber data dan metode pengambilan sampel digunakan dalam penelitian ini. Hasil penelitianmenunjukkan bahwa terdapat tanggapan positif dan negatif terhadap penggunaan konferensivideo sebagai alat bantu dalam pembelajaran bahasa Inggris. Terdapat tanggapan positifterkait penggunaan materi pada pertemuan daring melalui Microsoft Teams yaitu tanggapanpositif berdasarkan karakter siswa, serta tanggapan positif berdasarkan metode yangdigunakan dalam pertemuan Microsoft Teams. Selain itu, mahasiswa merasa lebih nyamandan menikmati pertemuan kelas secara daring karena dapat berhadapan langsung dengandosen secara virtual tanpa takut dikritik oleh mahasiswa lain. Di sisi lain, terungkap pulatanggapan negatif mengenai keterbatasan waktu yang diberikan khususnya dalam melatihketerampilan menulis, tanggapan negatif yang didasarkan pada karakter siswa, dantanggapan negatif mengenai kurangnya koneksi internet dalam melaksanakan proses belajarmengajar di Microsoft Teams.Kata kunci: Respon siswa, Pembelajaran jarak jauh, Microsoft Team Meeting